Occurrence of MCPD and glycidyl fatty acid esters in standard and specialised infant formula in Denmark. Issue 11 (1st November 2020) - Nguyen, Khanh Hoang; Fromberg, Arvid
ABSTRACT: Standard infant formula and specialised infant formula for medical purposes in Denmark (n = 42) were assessed for the levels of 2-MCPDEs, 3-MCPDEs, and GEs. Similar concentrations of GEs were observed in both standard and specialised powder infant formula at around 11.5 µg/kg. For 2-MCPDEs and 3-MCPDEs, significantly higher concentrations were observed in specialised products (18.0 and 49.8 µg/kg, respectively) in comparison with the standard ones (11.8 and 31.0 µg/kg, respectively). The concentration profiles also revealed discrepancies in MCPDEs and GEs concentrations not only between different manufacturers but also in terms of infant formula variety. For instance, the hypoallergenic powder formula showed twice as much MCPDEs as the normal formula variety. Exposure estimation using average contaminant concentrations in each variety suggested no potential risk of 3-MCPDEs and GEs intake for Danish infants via infant formula consumption. However, special attention is required for a few specific products where risks might occur in terms of 3-MCPDEs and/or GEs consumption.